(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In this article we intend to demonstrate the sources and results of the appearing of the intersected areas in grammatical and lexical word formation. How to teach English as a second or foreign language has been heatedly debated as long as the subject has been taught. One of the many issues regarding the teaching of English as a second or foreign language is the issue of whether or not to teach grammar, and if we teach it, how should we go about it?